A Physical Model for MOSFET Drain Current in Non-ohmic Regime Using Ohmic Regime Operation. (2001) - El Abbassi, A.; Amhouche, Y.; Raïs, K.; Rmaily, R.
Abstract : In order to characterise the velocity saturation phenomena in short channel MOSFET's, a simple method is proposed in this work. It is based on the comparison between transistor behaviour in ohmic and saturation regime respectively. Therefore, the MOSFET characteristicI d 0 ( V d ) . avoiding velocity saturation phenomena, can be obtained from ohmic characteristicI d ( V g ) and compared with the experimental characteristicI d ( V d ) .